Effect of family intervention on relapse rate of Chinese patients with alcohol-dependent - Wang, Yi-Jia; Tang, Shu-Si; Chen, Guang-Dong; Xia, Jin-Hong; Wang, Li-Na; Zhang, Huan-Le (Frontiers in Public Health, 2024)
Objective: This study explored the impact of a family intervention on the relapse rate of Chinese patients with alcohol dependence. Methods: A total of 151 male patients with alcohol dependence who were discharged from the Substance Dependence Department of the Wenzhou Seventh People's Hospital from January to December 2020 were selected. They were divided into the control (n=73) and experimental (n=78) groups. Patients in both groups received routine alcohol cessation treatment. Moreover, patients in the experimental group were followed up by a professional psychiatrist to carry out individual family intervention. The Family Function Rating Scale (FAD), a Self-made general information questionnaire, and the Chinese version of the Family Intimacy and Adaptability Scale (FACESI-CV) were performed. Re-drinking rate and readmission rate were assessed. Results: Family intervention could reduce relapse rate (31, 39.74%) and rehospitalization (27, 34.62%) compared with the control group. After family training, FAD factor scores were improved in the experiment group in comparison with the control group. Family training improved communication (18.2±3.7), role (20.8±2.5), emotional response (10.8±1.8), emotional involvement (13.7±1.2), behavioral control (19.8±1.2), and overall functionality (23.5±2.1) in the experiment group in comparison with the control group. After family training, intimacy (70.5±8.7) and adaptability (64.1±6.9) in the experiment group was higher than in the control group. After family intervention, Michigan Alcohol Dependence Scale (MAST) (9.21±0.68) and Short-Form 36 (SF-36) (80.32±4.47) in the experiment group were higher than the control group. Conclusion: Family intervention for families of patients with alcohol dependence can improve their family function, increase their family intimacy and adaptability, and reduce the rate of relapse.